2016
DOI: 10.1108/jmp-09-2014-0265
|View full text |Cite
|
Sign up to set email alerts
|

Silence as a mediator between organizational factors and stress

Abstract: Purpose The purpose of this paper is to investigate the mediating role of silence as a link between punishment, communication opportunities and stress. Design/methodology/approach The authors conducted a survey among 1,015 highly skilled employees of South Korean companies using a self-administered instrument. In total, 748 questionnaires were received from the 1,015 participants. Of these, 61 questionnaires were incomplete and were discarded; the remaining 687 questionnaires were used in the analysis. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
3
31
0
3
Order By: Relevance
“…The consequences of employee silence in the work context have yet to be exhaustively examined (M. Knoll et al., 2016; Morrison, 2014). Building on Morrison and Milliken’s (2000) theoretical framework and studies linking employee silence to stress (Dedahanov, Lee, & Rhee, 2016; Dedahanov, Lee, Rhee, & Yusupov, 2016), the present study sought to extend employee silence literature by identifying perceived stress as an underlying mechanism explaining the detrimental effects of employees withholding their opinions on behavioral outcomes. In addition, the study tested interpersonal trust as a boundary condition for the relationship between silence and stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequences of employee silence in the work context have yet to be exhaustively examined (M. Knoll et al., 2016; Morrison, 2014). Building on Morrison and Milliken’s (2000) theoretical framework and studies linking employee silence to stress (Dedahanov, Lee, & Rhee, 2016; Dedahanov, Lee, Rhee, & Yusupov, 2016), the present study sought to extend employee silence literature by identifying perceived stress as an underlying mechanism explaining the detrimental effects of employees withholding their opinions on behavioral outcomes. In addition, the study tested interpersonal trust as a boundary condition for the relationship between silence and stress.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from Dedahanov, Lee, Rhee, and Yusupov (2016) study indicated that employees restraining themselves from expression due to protecting their relationships and avoiding interpersonal conflict would experience discrepant beliefs which in turn results in elevated levels of stress. In another study, Dedahanov, Lee, and Rhee (2016) found that employees refraining from disagreement with their managers would experience increased levels of stress.…”
Section: Hypothesis Developmentmentioning
confidence: 95%
“…When employees experience destructive leadership, they have to spend more time and energy to struggle, survive, and preserve their limited resources, and thus they remain silent (Park et al, 2016). Because a leader is the recipient and disposer of the employees' opinions and voice within organisations, various motivations may cause individuals to rarely report or express their concerns and opinions on job-related issues to their supervisors (Dedahanov et al, 2016). From the perspective of COR theory (Hobfoll 1989), when subordinates are under a destructive leadership, they need to consume time and energy to cope with the stressful workplace event, instead of focusing on finding work problems and reporting them.…”
Section: Destructive Leadership and Employee Silencementioning
confidence: 99%
“…In organizations, successful management requires continuous feedback and input from lessons learned, however, ES impedes improvements and corrections (Dedahanov et al, 2016). It is a matter of prime importance to mitigate ES.…”
Section: Figure 2: Structural Model Resultsmentioning
confidence: 99%